Techno-Functional, Rheological, and Physico-Chemical Properties of Gelatin Capsule By-Product for Future Functional Food Ingredients - Sasina Sanprasert; Pudthaya Kumnerdsiri; Anusorn Seubsai; Piyangkun Lueangjaroenkit; Jaksuma Pongsetkul; Sylvia Indriani; Tanyamon Petcharat; Samart Sai-ut; Kanrawee Hunsakul; Utthapon Issara; Subhash V. Pawde; Saroat Rawdkuen; et al. (Foods)
The utilization of gelatin capsule waste (GCW) poses a challenge for the industry. This study investigates its potential as a functional food ingredient by evaluating the physico-chemical, rheological, and techno-functional properties of gelatin capsule waste powder (GCWP). To achieve this, the gelatin capsule waste (GCW) was mixed with maltodextrin at varying ratios (1:1, 1:2, 1:3, 1:4, and 1:5) and subjected to spray drying. The findings highlight maltodextrin’s crucial role in stabilizing the drying process, reducing stickiness, and enhancing handling and storage properties. All the obtained GCWP samples appeared light white and had a slightly sticky texture. The 1:5 (w/w) GCW-to-maltodextrin ratio produced the highest powder recovery with minimal stickiness, indicating enhanced drying efficiency. Increasing maltodextrin reduced gel strength, texture, and foaming properties while raising the glass transition temperature. The FTIR analysis indicated a decline in protein–protein interactions and increased polysaccharide interactions at higher maltodextrin levels. The rheological analysis demonstrated lower elastic and loss moduli with increased maltodextrin, affecting GCWP’s structural behavior. For overall properties, the GCW mixed with maltodextrin at a 1:1 ratio (GCW-1M) is recommended for future applications, particularly for its gelling characteristics. The GCW-1M, being rich in amino acids, demonstrates its potential as a functional food ingredient. However, certain properties, such as gel strength and powder stability (hygroscopicity and stickiness), require further optimization to enhance its industrial applicability as a functional food ingredient.